Cost-Consequence Analysis of Levofloxacin Compared to Ceftriaxone in Community-Acquired Pneumonia of Adult Inpatients at X Hospital Surakarta - Rolando Rahardjoputro; Adhi Wardhana Amrullah; Joko Santoso; Hanugrah Ardya Crisdian Saraswati; Ernawati; Hutari Puji Astuti; Mellia Silvy Irdianty; Rufaida Nur Fitriana (Universitas Airlangga, 2024)
Background: Community-acquired pneumonia is still a significant cost-burden disease in healthcare facilities. Pharmacoeconomic analysis using the cost-consequence analysis (CCA) method of ceftriaxone compared to levofloxacin as a first-line empirical antibiotic has never been carried out. Objective: to model the clinical and economic impact of administering ceftriaxone as a first-line empirical antibiotic compared to its comparator levofloxacin for community-acquired pneumonia therapy in hospitalized adult inpatients from the perspective of healthcare facilities. Methods: This research is a retrospective observational study that collects medical records and patient billing data in X Hospital Surakarta from January to December 2022 period. The study was conducted from June to July 2023. Subjects were adult inpatients aged ≥ 18 years with community-acquired pneumonia and were given levofloxacin or ceftriaxone as first-line empiric antibiotics. The data taken included patient profile, antibiotic effectiveness and direct medical costs. Cost-consequence analysis (CCA) was used to compare levofloxacin to ceftriaxone to assess their impact on length of stay, antibiotic effectiveness, and direct medical costs based on a healthcare perspective. Results: The antibiotic effectiveness for levofloxacin was 75.00%, and ceftriaxone was 93.33%. The average length of stay for levofloxacin was 3.39 days, and ceftriaxone was 3.00 days. The total direct medical costs for levofloxacin were IDR 2,056,799, and ceftriaxone was IDR 1,969,627. Conclusion: The administration of ceftriaxone to levofloxacin as a first-line empirical antibiotic for community-acquired pneumonia in hospitalized adult patients had the consequence of increasing antibiotic effectiveness, reducing the length of stay and saving total direct medical costs by IDR 87,172.